Inflammasome activation and IL-1β target IL-1α for secretion as opposed to surface expression - Fettelschoss, Antonia (National Academy of Sciences, 2011)
Interleukin-1α (IL-1α) and -β both bind to the same IL-1 receptor (IL-1R) and are potent proinflammatory cytokines. Production of proinflammatory (pro)–IL-1α and pro–IL-1β is induced by Toll-like receptor (TLR)-mediated NF-κB activation. Additional stimulus involving activation of the inflammasome and caspase-1 is required for proteolytic cleavage and secretion of mature IL-1β. The regulation of IL-1α maturation and secretion, however, remains elusive. IL-1α exists as a cell surface-associated form and as a mature secreted form. Here we show that both forms of IL-1α, the surface and secreted form, are differentially regulated. Surface IL-1α requires NF-κB activation only, whereas secretion of mature IL-1α requires additional activation of the inflammasome and caspase-1. Surprisingly, secretion of IL-1α also required the presence of IL-1β, as demonstrated in IL-1β–deficient mice. We further demonstrate that IL-1β directly binds IL-1α, thus identifying IL-1β as a shuttle for another proinflammatory cytokine. These results have direct impact on selective treatment modalities of inflammatory diseases.